Student’s Ability In Reading The Yellow Book To Prepare The Religious Judge Candidates In Universitas Islam Negeri Sumatera Utara (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2022)
The purpose of this study was to find out the student’s reading ability and the problems students face in understanding yellow books. This study used a descriptive qualitative research method. This study's subjects were the department head, lecturers, and students of Al-Ahwal al-Syakhsiyah UIN Sumatera Utara. The source of data was used primary and secondary. Data collection was done by interview, observation, test, and documentation. Data analysis was carried out by having some steps: data display, data reduction, and conclusion. The results showed that of 77 students, there were 15 students were excellent at reading the yellow book, and 13 had inferior ability in reading the yellow book. The method used in learning the yellow book was the combination method. However, there were problems faced by students in understanding the yellow book, such as the lack of academic activities based on the yellow book recitation and the number of students who did not have the basic knowledge of mastering the yellow book. It was found that some supporting and inhibiting factors in learning yellow book in UIN Sumatera Utara, especially for students of Al-Ahwal al-Syakhsiyah.